Performance of The Member of Orchid Consortium Mailing List - Dyah Gandasari; Sarwititi Sarwoprasodjo; Basita Ginting; Djoko Susanto (Jurnal Komunikasi Pembangunan, 2014)
AbstractIssues such as collective natural resource management, chain management and multi-functional agriculture requires new forms of coordinated action and cooperation between farmers and other stakeholders. Orchid consortium is a new cooperation system developed as an attempt to synergize various drive components in the orchid floriculture development in Indonesia. The mailing list as one of the collaborative information and communication systems is built to share information among members of the orchid consortium. The research objectives are: (1) To identify communication interaction process of the current performance of the orchid consortium. (2) To identify in which stage of the current performance of the orchid consortium. The unit of analysis is messages in the consortium mailing list. This research resulted several outputs i.e: (1) Technical and organizational themes are the most widely discussed in the mailing list of orchid consortium, (2) Group members were still in the stage of knowing each other and exp lain ideas or still in the orientation phase.Keywords: information systems, consortium, orchid, floriculture